2010
DOI: 10.3791/2170
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Rodent Whole Embryo Culture using the Rotator-type Bottle Culture System

Abstract: Whole embryo culture (WEC) technique has been developed in 1950's by New and his colleagues, and applied for developmental biology 1 . Although development and growth of mammalian embryos are critically dependent on the function of the placenta, WEC technique allows us to culture mouse and rat embryos ex vivo condition during limited periods corresponding to midgestation stages during embryonic day (E) 6.5-E12.5 in the mouse or E8.5-E14.5 in the rat 2, 3, 4 . In WEC, we can directly target desired areas of emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Rat serum was prepared by immediate centrifugation of rat blood (IC serum) as described for ex vivo culture of mouse post-implantation embryos (Takahashi and Osumi, 2010). In our experiments, freshly isolated IC serum from overnight-fasted rats or commercially available rat IC serum improved survival of cultured embryos.…”
Section: Development Of In Vitro Chimera Assaymentioning
confidence: 99%
“…Rat serum was prepared by immediate centrifugation of rat blood (IC serum) as described for ex vivo culture of mouse post-implantation embryos (Takahashi and Osumi, 2010). In our experiments, freshly isolated IC serum from overnight-fasted rats or commercially available rat IC serum improved survival of cultured embryos.…”
Section: Development Of In Vitro Chimera Assaymentioning
confidence: 99%
“…1 embryos dissected at either 7.5 or 8.5 dpc and cultured in CRSD had overt signs of abnormal development, whereas those cultured in CRSFN appeared to develop to the equivalent in utero stage. Embryos that are grown in culture for 24 hours from the late primitive streak stage (7.5 dpc) are expected to develop ~ 6 somites and to exhibit morphological landmarks of cranial neural development (Downs and Davies 1993;Kaufman and Bard 1999;Rivera-Perez et al, 2010;Takahashi and Osumi 2010;Van Maele-Fabry et al, 1993). The majority of embryos cultured in CRSD did not develop somites and their allantois often protruded through the yolk sac.…”
Section: Resultsmentioning
confidence: 99%
“…The development of murine WEC protocols therefore focused on achieving reasonable culture success using rat serum (since one rat typically yields sufficient sera to culture twenty embryos (Hunter et al, 1988)). A number of studies have shown that rat serum supports ex utero growth of post-implantation stage mouse embryos for at least 24 hours, providing that blood is withdrawn from the animal gently, immediately centrifuged, the fibrin clot carefully removed, and the sera heat-inactivated (Cockroft 1991;Harris 2012;New 1978;New et al, 1976;Piliszek et al, 2011;Rivera-Perez et al, 2010;Steele and New 1974;Takahashi and Osumi 2010;Tam and Snow 1980;Van Maele-Fabry et al, 1991). The exacting requirements for the production of mouse embryo-culture-grade rat serum means commercial preparations are generally not able to support the ex utero growth of mouse embryos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In WEC, mouse and rat embryos can grow ex vivo, (i.e., outside of the uterus). Although the WEC technique was often used in teratology by adding various chemical compounds into the culture medium, this technique has also been used in various developmental biology studies to examine unique developmental mechanisms in mammals [2][3][4] . For example, WEC is combined with other techniques, such as cell labeling, in wild-type and mutant embryos by using fluorescent dye 5 , cell transplantation 6 , and gene introduction via lipofection 7 and electroporation [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%